الشعرانية - دراسة سببية خبرة مشفى الأسد الجامعي في اللاذقية - درويش, علي; المرعي, منيف; دواي, رنا (Latakia University Journal -Medical Sciences Series, 2019)
تعتبر الشعرانية من المشكلات الرئيسة التي تعاني منها كثير من الإناث خاصة في منطقتنا المتوسطية وعلاجها يعتمد على السبب وهنا تكمن أهمية معرفة هذه الأسباب. في هذه الدراسة تمت دراسة أسباب الشعرانية لدى 100 امرأة اللاتي راجعن مشفى الأسد الجامعي في اللاذقية في عامي 2005-2006. تم التشخيص اعتماداً على القصة المرضية والدوائية و العائلية والفحص الدقيق وعيار الهرمونات الآتية: التستوسترون الحرFT ودي هيدروابي اندروسترون سلفاتDHEA-s و17 هدر وكسي بروجستيرون 17OHP والبرولاكتين والهرمون المنبه للجريب FSH والهرمون اللوتيني LH والهرمون المنبه للغدة الدرقية TSHوالكورتيزول وفي حالة الضرورة تم إجراء اختبار تحريض الACTH لتشخيص فرط تنسج الكظر الخلقي غير النموذجي بالإضافة إلى إيكوغرافي للحوض والكظرين وطبقي محوري عند الضرورة فكانت النتائج: شعرا نية أساسية 57% - مبيض متعدد الكيسات 39% - عوز21 هدروكسيلاز 2% -ورم مبيضي 1% - قصور درقي1%. Hirsutism is considered major problem from which many women suffer, especially in our Mediterranean region. Treatment depends on the cause; so knowing the cause o hirsutism is important. In this study, we search for the causes of hirsutism in100 women consulting Al-Assad University Hospital, Lattakia, in 2005 and 2006. Diagnosis depends on medical and familial history. Careful examination and tests for free testosterone FT, dehydroepiandrosterone–sulphate DHEA-s, 17 hydroxy progresterone 17OHP, prolactin, follicle–stimulating hormone FSH Luteinizing hormone LH, cortisol, thyroid stimulating hormone and ACTH stimulating test were performed. The diagnosis of non–congential adrenal hyperplasia NCAH, pelvic and adrenal ultrasoungraphies was performed and abdominal computed tomography was performed in some cases. The results showed idopathic hirsutism %57, poly cystic ovary syndrome %39, 21 hydroxylase defficiency %2, ovarian tumor %1, and thyroid dysfunction %1.